Breast-feeding, Leptin: Adiponectin Ratio, and Metabolic Dysfunction in Adolescents with Obesity. Issue 5 (May 2017) - Mihalopoulos, Nicole L.; Urban, Brittney M.; Metos, Julie M.; Balch, Alfred H.; Young, Paul C.; Jordan, Kristine C.
Abstract : Objectives: Increased adiposity increases leptin and decreases adiponectin concentrations, resulting in an increased leptin:adiponectin ratio (LAR). In adults, components of the metabolic syndrome and other cardiometabolic risk factors, what we classify here as "metabolic dysfunction, " are associated with both a high LAR and a history of being breast-fed. The relation among breast-feeding, LAR, and degree of metabolic dysfunction in obese youth is unknown. The purpose of our pilot study was to explore this relation and estimate the effect size of the relations to determine the sample size needed to power future prospective studies. Methods: We obtained fasting levels of leptin, adiponectin, lipids, insulin, and glucose from obese youth (aged 8–17 years). Weight, height, waist circumference, blood pressure, and breast-feeding history also were assessed. Results: Of 96 participants, 78 were breast-fed as infants, 54% of whom were breast-fed for >6 months. Wide variation was observed in LARs among children who were and were not breast-fed (>100% coefficient of variation). Overall, prevalence of metabolic dysfunction in the cohort was 94% and was not proven to be associated with higher LAR. Conclusions: In this cohort of obese youth, we found a high prevalence of breast-feeding, metabolic dysfunction, and wide variation in the LARs. Based on the effect size estimated, future studies would need to enroll >1500 patients or identify, stratify, and selectively enroll obese patients without metabolic dysfunction to accurately determine whether breast-feeding in infancy influences LARs or metabolic dysfunction among obese youth. Abstract : The authors explored the relation between breast-feeding in infancy and a lower leptin:adiponectin ratio and metabolic dysfunction in adolescents (8 to 17 years old) with obesity. They also estimated the effect size of the relations to determine the sample size needed for future prospective studies.